The Study on Curriculum for Thai Language Teaching at Elementary Education Level of Schools in Local and Ethnic Areas in the North - พูลพิพัฒน์ นราวัลย์; ฤกษ์สมบูรณ์ดี สุรางคนา; ศิริสวัสดิ์ ปทุมวดี; วงศ์ทิพย์ กิตติพงษ์; สมนาม สิระ (Ganesha Journal, 2018)
The objectives of this research were to 1) study the development of Thai teaching curriculum at elementary school level and the implementation of the curriculum in local schools and schools in ethnic areas in the North, 2) study the method of instructional provision for Thai reading and writing at elementary school level of local schools and schools in ethnic areas in the North, and 3) study the results of implementing the curriculum and instructional provision for Thai reading and writing at elementary school level of local schools and schools in ethnic areas in the North. The research sample included the local schools affiliated with the local administrative organization, the schools in ethnic areas, affiliated with the Office of the Basic Education Commission, superintendents, teachers, teachers who had received teaching award, Prathom Suksa 3 students, and Prathom Suksa 6 students. The research instruments included forms for analyzing the curriculum, forms for analyzing Thai instructional plans, forms for interviewing the teachers and the superintendents, forms for observing class rooms, test on the student’s reading and writing Thai, and the issues for the small group discussion. The data was analyzed in term of mean, standard deviation, percentage. The research findings were as follows: 1) The development of Thai language teaching curriculum at elementary school level of local schools and schools in ethnic areas in the North could be divided in 6 periods and the Implementation of the Curriculum in Local Schools and Schools in ethnic areas in the North was found that every school in the country has used 2008 Thai language strand core-curriculum and confined to the structure and learning strands set by the Ministry of Education. 2) The teacher’s instructional method for teaching reading and writing Thai was found that there were about 9 methods. From the interviewed, the most teachers similarly contended that the factors leading to successful instruction on reading and writing were the teacher’s time devotion and energy for helping the students to be able to read and write. 3) Prathom Suksa 3 students of the local schools had learning achievement in pronouncing the vocabularies assigned, the writing for the word for the given picture, the sentence writing and the analytical reading higher than Prathom Suksa 3 students of the schools in ethnic areas. Prathom Suksa 6 students of the local schools had learning achievement in the sentence writing and the analytical reading higher than Prathom Suksa 6 students of the schools in ethnic areas but had the learning achievement in pronouncing the vocabularies assigned, the writing for the word for the given picture less than Prathom Suksa 6 students of the schools in ethnic areas.